Clinical and quality of life improvement after bilastine treatment among patients with autoimmune chronic spontaneous urticaria - My Tra Thi Nguyen; My Huyen Le; Minh Nguyet Vu; Katrine Baumann; Per Stahl Skov; Doanh Huu Le (PLoS ONE, 2025)
Background This study aimed to evaluate the clinical effectiveness of bilastine in type IIb autoimmune CSU (type IIb aiCSU) patients over an 8-week period, as well as to identify factors predicting treatment response. Method 34 type IIb aiCSU patients with positive basophil histamine release assays (BHRA) and positive Autologous Serum Skin Test (ASST) tests, from the Vietnam National Dermatology and Venereology Hospital, were included. Patients began treatment with the standard dose of bilastine, with the dose increased every two weeks for those who did not achieve adequate response. The Urticaria Control Test (UCT), Weekly Urticaria Activity Score (UAS7), and the Chronic Urticaria Quality of Life Questionnaire (CU-Q2oL) were used. Results Significant improvements in all measures were observed, with 82.4% of patients achieving complete response by week 8. Of these, 47.1% responded to the standard dose, while 14.7% did not respond even at the maximum (x4) dose. UAS7 average scores decreased from a baseline mean of 28.9 to 2.9, indicating substantial reduction in disease activity. UCT scores improved from 47.1% of patients having poor disease control (UCT < 12) after week 2 to 85.3% achieving good control (UCT ≥ 12) by week 8. QoL also significantly improved, with CU-Q2oL scores dropping from 44.9 at baseline to 25.3 at week 8. Basopenia, high baseline UAS7 score and a history of autoimmune disease were associated with poorer treatment responses, while normal/high IgE levels were linked to better outcomes. Conclusion The findings suggest that bilastine is highly effective in controlling aiCSU symptoms and improving QoL.